2020
DOI: 10.1101/2020.02.11.943431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ant guards influence the mating system of their plant hosts by altering pollinator behaviour

Abstract: 31Ant guards can increase plant fitness by deterring herbivores but may also 32 reduce it by interfering with pollination, hence ant-plant interactions are ideal 33 systems in which to study costs and benefits of mutualisms. While ant impacts 34 on herbivory are well-studied, much less is known about impacts on 35 pollinators and associated consequences for plant mating systems and fitness. 36 We used field experiments to quantify the effect of ant guards on pollinator 37 community composition, freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Visitors spent in average less time per flower in AA than in the other three treatments. Time is another important variable related to plant fitness, leading to a decrease in pollen removal and fruit set (Calixto et al under review) or an increase in cross-pollination, which can lead to an increase of fruit set (Villamil et al, 2020). For instance, Calixto et al (under review) showed that more aggressive ants can significantly decrease the time spent by pollinators when visiting flowers, resulting in a significant decrease of fruits produced in Qualea multiflora (Vochysiaceae).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visitors spent in average less time per flower in AA than in the other three treatments. Time is another important variable related to plant fitness, leading to a decrease in pollen removal and fruit set (Calixto et al under review) or an increase in cross-pollination, which can lead to an increase of fruit set (Villamil et al, 2020). For instance, Calixto et al (under review) showed that more aggressive ants can significantly decrease the time spent by pollinators when visiting flowers, resulting in a significant decrease of fruits produced in Qualea multiflora (Vochysiaceae).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Calixto et al (under review) showed that more aggressive ants can significantly decrease the time spent by pollinators when visiting flowers, resulting in a significant decrease of fruits produced in Qualea multiflora (Vochysiaceae). On the other hand, Aguirre-Jaimes et al (2018) showed that the effective pollinator of Vigna luteola (Fabaceae) spent less time visiting flowers in order to avoid ant predation, which might result in an increase of fruit set; and Villamil et al (2020) observed in Turnera velutina (Passifloraceae) that ants decreased pollinator foraging time and flower visit duration, but increased outcrossing rates. Given that, it seems that the time spent by pollinators can have different effects depending on the system that they are involved, resulting in negative, neutral, or positive effects to plants (Gonzálvez et al, 2013;Sousa-Lopes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although there seems to be a clear negative effect of the presence of ants when foraging on flowers on pollinator behavior, a few studies have shown positive outcomes [ 23 , 33 , 51 , 54 ]. Decreasing pollinator visitation to flowers in response to the presence of ants may lead to decreased self-pollination or may increase the likelihood of cross-pollination, as pollinators are forced to constantly change flowers within plants and/or to move to other plants due to the presence of ants [ 23 , 33 , 51 , 54 ]. In this context, there is a decrease in the foraging efficiency of pollinators on the same plant individual but an increase in movement between individual plants, bringing positive effects for plant reproductive success.…”
Section: Positive Effects Of Pollinator Repellence By Antsmentioning
confidence: 99%
“…Knowing the identity of the ants, herbivores, plants, and pollinators can be essential to understanding the levels of protection and pollination disruption established. More aggressive ants are expected to provide better protection to plants against herbivore attack, but at the same time they can have a greater influence on pollination processes than less aggressive ants, showing context-dependent outcomes [ 54 , 101 , 102 , 103 , 104 ].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%